2019
DOI: 10.1080/0142159x.2018.1562166
|View full text |Cite
|
Sign up to set email alerts
|

Non-technical skills assessments in undergraduate medical education: A focused BEME systematic review: BEME Guide No. 54

Abstract: Background Many medical schools have implemented curricula to teach non-technical skills, a personal set of complex social and cognitive skills which are grounded in human factors safety industries in and out of health. Consensus on how to assess these skills is lacking. This systematic review aimed to evaluate the evidence regarding non-technical skills assessments in undergraduate medical education, to describe the tools used, learning outcomes and the validity, reliability and psychometrics of the instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 36 publications
0
36
0
5
Order By: Relevance
“…The review team postulated, in line with previous BEME reviews, that this is partly related to the complexity of educational developments and therefore requires an approach that can address and account for this complexity. Thus, we considered two distinct quality elements: 1) the risk of bias or quality of the study design when outcomes were reported (similar to the Cochrane tradition) and 2) the risk of bias or quality of reporting for the educational development itself (as previously used by Gordon, Farnan, et al (2019) and Gordon et al (2018), originally modified from Reed et al (2005)). The latter is critically important, because only when the development is robustly described, can educators or researchers hope to replicate the results in other contexts.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The review team postulated, in line with previous BEME reviews, that this is partly related to the complexity of educational developments and therefore requires an approach that can address and account for this complexity. Thus, we considered two distinct quality elements: 1) the risk of bias or quality of the study design when outcomes were reported (similar to the Cochrane tradition) and 2) the risk of bias or quality of reporting for the educational development itself (as previously used by Gordon, Farnan, et al (2019) and Gordon et al (2018), originally modified from Reed et al (2005)). The latter is critically important, because only when the development is robustly described, can educators or researchers hope to replicate the results in other contexts.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…This is in keeping with a recent Best Evidence in Medical Education (BEME) systematic review of NTS assessments in medical education, which noted that failure to incorporate NTS training within medical students' education could result in the undervaluing of the area by students. 9 The medical students in this study described a clear transition in their perspectives on NTS and the impact of such skills on patient care, and articulated how this change of perspective might influence their future behaviour (Phases 5 and 6).…”
Section: Discussionmentioning
confidence: 90%
“…In its Generic Professional Capabilities Framework, the UK General Medical Council outlines the necessity for doctors to demonstrate and apply NTS to improve the quality and safety of patient care . It is recognised that training in NTS should be incorporated into the curricula of medical students, but the lack of consensus or recommendations with reference to such training has resulted in significant heterogeneity in approaches to teaching such skills . Furthermore, the way in which such teaching interventions have been evaluated is also variable.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of these human factors on clinical outcomes has already been ascertained [37, 38]. In the undergraduate setting, however, there is a substantial lack of guidance and teaching for these skills [39, 40]. Our stakeholders underlined the need to teach human factors, which might represent a trend that is already occurring in the postgraduate medical education milieu , as a shift towards a more holistic model of medical education.…”
Section: Discussionmentioning
confidence: 99%